ANALISIS PEMASARAN MAGGOT BSF (BLACK SOLDIER FLY) POKDAKAN TIRTA BALI MAGGOT - Saverius Anggal; Edvin Jericho Timbu Tana; Nyoman Yudiarini; Luh Putu Kirana Pratiwi; I Gusti Ayu Diah Yuniti (AGRIFARM (Jurnal Agribisnis dan Sosial Ekonomi Pertanian), 2023)
Organic waste is often not processed properly, so it accumulates and pollutes the environment. Therefore, cultivating BSF (Black Soldier Fly) maggots as a decomposer of organic waste can be a solution to reduce organic waste while also having the potential to increase people's income through marketing BSF maggots as animal feed. This research aims to determine the marketing mix of BSF maggots in Pokdakan Tirta Bali Maggot using descriptive methods. The research results show that there are seven factors that influence the marketing mix, namely product, price, promotion, place, people, process and physical evidence. The main obstacle to marketing BSF maggots alive is that there must be special treatment in the distribution process. In terms of business development and cost efficiency in pakat production, BSF maggot has great potential if it is developed into pellets as fish feed